Effectiveness of Microenterprise Law to Registered Microenterprises: Quantitative Assessment in The Philippines - Manipol, Vergel S. (Future Science / FSH-PH Publications, 2023)
Microenterprises as seabeds of a promising business tycoon, like how the world of entrepreneurship should be seen - call a lot of attention and cultivation. In 2002, the Philippine government passed a law granting incentives and benefits to registered microenterprises. However, since then, no thorough evaluation has been done to create a precise quantification and result. The study's purpose is to determine the effectiveness of Barangay Micro-business Enterprise Law on microenterprises and to use it as a global reference concerning the effectiveness of similar government law as practiced by the rest of the world. Descriptive-correlational method of research utilizing quantitative data was used that led to the conclusion that BMBE Law was generally effective to microenterprises with a weighted mean of 4.1769; this means that the law has been effective and useful to the beneficiaries making its two incentives (out of 5) very effective.